Sharing Styles: New Media, Creative Communities and the Evidence of an Open Source Design Movement - Gregory Turner-Rahman (Fibreculture Journal, 2005)
This article derives from an ethnographic study of online creative communities and, more specifically, it explores the sharing of resources and knowledge in design culture websites. Design culture encompasses a number of creative disciplines - Web design, graphic design, industrial design, architecture, fashion, filmmaking and even music – and is marked by the production and consumption of exploratory interdisciplinary work intended for others in the community and not for broader corporate commercial application. Design culture websites often provide links to inspirational projects, resources, tools, how-to discussions, communal projects and small-scale e-commerce sites targeting other designers.